Irisin: A New Code Uncover the Relationship of Skeletal Muscle and Cardiovascular Health During Exercise - Ma, Chunlian; Ding, Haichao; Deng, Yuting; Liu, Hua; Xiong, Xiaoling; Yang, Yi (Frontiers in Physiology, 2021)
Exercise not only produces beneficial effects on muscle itself via various molecular pathways, but also mediates the interaction between muscles and other organs in an autocrine/paracrine manner through myokines, which plays a positive role in maintaining overall health. Irisin, an exercise-derived myokine, has been found involved in the regulation of some cardiovascular diseases. However, the relationship between irisin and cardiovascular health is not fully elucidated and there are some divergences on the regulation of irisin by exercise. In this review, we present the current knowledge on the origin and physiology of irisin, describe the regulation of irisin by acute and chronic exercises, and discuss the divergences of the related research results. Importantly, we discuss the role of irisin as a biomarker in the diagnosis of cardiovascular diseases and describe its treatment and molecular mechanism in some cardiovascular diseases. It is expected that irisin will be used as a therapeutic agent to combat cardiovascular diseases or other disorders caused by inactivity in the near future.